Analysis Of Job Satisfaction Influenced By Compensation, Organizational Culture And Performance - Jefverson, Jefverson; Aris Budiono (SEAN Institute, 2024)
This research aims to analyze job satisfaction which is influenced by compensation, organizational culture and performance. The research location was carried out at an accommodation service called Novotel Makassar Grand Shayla in February 2024, and the research population was 130 people. Sampling used a Likert scale instrument as a direction for carrying out measurements. Saturated Sampling Method after subtracting 20 respondents to test validity and reliability. A total of 100 respondents who are willing to fill out the questionnaire will be used in multiple linear regression calculations using the SEM-PLS software application. The findings are as follows: job satisfaction is influenced by compensation, job satisfaction is influenced by organizational culture, and job satisfaction is not influenced by performance.